Assessment of microplastic characterization and distribution from surface water and the seabed in the Flores Sea, Indonesia - Herawati, Titin; Damayanti, Windi; Yuda, Givanka A.; Ihsan, Yudi N.; Pasaribu, Buntora; Harsono, Gentio; Marlina, Marlina; Suseno, Heny; Mustopa, Rizki A.; Karya, Felin S. W.; Febriani, Choerunnisa; Purba, Noir P. (Frontiers in Marine Science, 2024)
Despite growing global concerns, there has been limited research on the characterization and distribution of microplastics in the Indonesian Throughflow (ITF) pathways, such as the Flores Sea. The Flores Sea is a component of the Indian–Pacific Current, a significant ocean current system that links the Pacific and Indian oceans and has the capacity to carry pollution over large marine ecosystems, making this research extremely important. Understanding the microplastic pollution in this area informs local environmental management. It provides insights into how these currents may distribute microplastics (MPs) across regional and global scales, impacting marine life and human health far beyond the immediate area. To respond to these concerns, this research aims to determine the characterization and distribution of MPs at six research sites in the Flores Sea that are precisely located within the ITF. This work exhibits an extensive dataset focusing on the occurrence, attributes, and dispersion of microplastics in the Flores Sea. The water sampling was carried out during a Jala Citra 3 by the Indonesian Navy from April to May 2023. Sea surface water samples were collected using a Neuston net, while sediment samples were taken from three stations at the shallowest depth using the Ekman Grab sampler. Additionally, abundance, size, shape, and color analyses were conducted using a light microscope, and microplastic types were identified through Raman spectroscopy. The results indicated that the Flores Sea waters and sediment are polluted with microplastics, with relative abundances ranging from 0.75 ± 0.49 to 2.13 ± 0.25 items/l samples. The most dominant shapes identified were filament (77.45%) and fragment (13.40%), with sizes varying between surface water 4.70 to 3799.25 μm and seabed from 67.20 mm to 2176.87 mm, while black (30.07%) and blue (24.51%) were reported as the common MPs colors. The identified polymers include PET and PE. This study confirms visual evidence of microplastics in the open waters of eastern Indonesia. While it may not fully capture the wide range of temporal variations, it establishes initial microplastic presence and dispersion levels. Given that the ITF influences both the Pacific and Indian Oceans, this research contributes to the global understanding of microplastic distribution across ocean basins, underscoring the need for coordinated international efforts to address marine pollution.